Measuring Residential Satisfaction in Historic Areas Using Actual-Aspiration Gap Theory: The Case of Famagusta, Northern Cyprus - Davoodi, Tina; Yapicoglu, Balkiz; Dagli, Ugur Ulas (Mdpi, 2023)
Although historical areas have significant unique architectural, historical and cultural values, and urban patterns, the physically degraded/damaged and deteriorated urban fabric of historical environments does not completely fulfill the contemporary needs of residents, which leads to low levels of resident satisfaction. As a result, this study examines the factors affecting residential satisfaction in a historic area to enhance satisfaction. Toward this objective, the present study selects the historical area of Famagusta, North Cyprus, and conducts a comprehensive survey among 129 households. Furthermore, the present study assesses residential satisfaction by incorporating socio-demographic, household environment, local historic housing renovation rules, and sense-of-place factors as well as applying the logit regression approach to find reliable results. Moreover, this study performs bootstrap Least Absolute Shrinkage and Selection Operator (LASSO) logistic regression to rank the importance of variables instead of relying on the size of estimated coefficients. To the best of our knowledge, this is among the first studies to conduct this nexus and the results could significantly contribute to the literature. Remarkably, the results reveal that the residential environment, local historical housing renovation rules, and sense of place have significant and positive effects on residential satisfaction, implying that these factors have a significant role in raising residents' satisfaction levels.
Keywords: residential satisfaction; historic environment; sense of place; walled city; absolute shrinkage and selection operator (LASSO)